Public Attitudes About Normal and Pathological Grief - Penman, E.; Breen, Lauren; Hewitt, Lauren; Prigerson, H. (Routledge, 2014)
Determining public expectations of grief is an important contributor to the debate differentiating normal from pathological grief. An international sample of 348 participants was randomly allocated to 1 of 12 conditions comprising a bereavement vignette and self-report items measuring grief expectations and social distance. Participants expected grief to decrease steadily between 2 weeks and 6 months then stabilize; however, time did not affect social distance. Gender of the bereaved and circumstances of death did not influence expectations, but did interact to influence social distance. These factors must be accounted for in determining a deviation from the norm in diagnostic nosology.